An Understanding of communities of singers in the context of a funeral ceremony in Bontoc, Mountain Province, Philippines (Musika Jornal, 2011)
The study focuses on an ethnography of two communities of singers in Bontoc, Mt. Province, namely, a community of contemporary singers called Tokwifi and a community of traditional singers. It describes the formation, role, repertoire, and cultural orientation of two communities of singers in the context of a funeral ceremony held in December 2006. Influenced by Christopher Small's concept of "musicking," the study provides an understanding of how communities of singers participate in an event such as a funeral wake and create meaning in relation to social obligations within the family and larger Bontoc community. Central in the performance of the two communities of singers is a vocal genre called antoway. Antoway are songs for the dead rendered during wakes for people who died at an old age. In the funeral ceremony under study, the antoway are performed in two different modalities. Religious, social, and political beliefs and how they are interpreted individually or collectively as a community reflect the mode through which beliefs are expressed.